2022
DOI: 10.3389/fcimb.2022.841741
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Monocyte-Like Myeloid Derived Suppressor Cells and CD16 Positive Monocytes Correlate With Immunological Responsiveness of Tuberculosis Patients

Abstract: Alterations of myeloid cell populations have been reported in patients with tuberculosis (TB). In this work, we studied the relationship between myeloid-derived suppressor cells (MDSC) and monocytes subsets with the immunological responsiveness of TB patients. Individuals with active TB were classified as low responders (LR-TB) or high responders (HR-TB) according to their T cell responses against a cell lysate of Mycobacterium tuberculosis (Mtb-Ag). Thus, LR-TB, individuals with severe disease, display a weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…All nucleated cells produce cytokines with either antagonistic or synergistic effects 11 depends on the infection milieu and the host-pathogen interaction. The release of Th1 and Th17 inflammatory cytokines (IL-2, www.nature.com/scientificreports/ TNF-α, IFN-γ, IL-12 and IL-17) are correlated with host protective responses against TB infection 27,28 and that was in connection with MTB clearance and sterilization of granulomas in macaques 17 . The so-called protective cytokines switch to pathological responses due to their overproduction and loss of balance in DR-TB and DS-TB from our study as stated earlier by Kumar et al, 2019 where the type 1 and 17 cytokines assist disease pathology in PTB 8 .…”
Section: Discussionmentioning
confidence: 99%
“…All nucleated cells produce cytokines with either antagonistic or synergistic effects 11 depends on the infection milieu and the host-pathogen interaction. The release of Th1 and Th17 inflammatory cytokines (IL-2, www.nature.com/scientificreports/ TNF-α, IFN-γ, IL-12 and IL-17) are correlated with host protective responses against TB infection 27,28 and that was in connection with MTB clearance and sterilization of granulomas in macaques 17 . The so-called protective cytokines switch to pathological responses due to their overproduction and loss of balance in DR-TB and DS-TB from our study as stated earlier by Kumar et al, 2019 where the type 1 and 17 cytokines assist disease pathology in PTB 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Cut-off values to differentiate be-tween the two populations of LR TB and HR TB patients were previously established by Pasquinelli et al and Amiano 2022 [26,27]. The fulfilment of two of the three mentioned criteria was required to assign a patient to the corresponding group [26,27]. Besides, it was demonstrated that common clinical parameters analyzed in TB patients paralleled immunological criteria studied in HR and LR individuals [7,26].…”
Section: Empowering Immune Endotypes That Endorse the Clinical Phenot...mentioning
confidence: 99%
“…The results of studies on TB patients also confirm the correlation between MDSCs and disease ( Table 2 ). The frequency of both subpopulations of MDSCs was elevated in PBMC of patients with active TB, was dominated by M-MDSCs, reduced the immunological function of lymphocytes in TB patients, and was proportional to the severity of the disease ( 67 70 ). Other investigations have shown that the levels of PMN-MDSCs are elevated in the peripheral blood and bronchoalveolar lavage fluid of patients with active TB, and that these levels correlate with plasma nitric oxide levels ( 6 , 72 ).…”
Section: Mdscs As a Target For Infectious Lung Diseasesmentioning
confidence: 99%